2017
DOI: 10.1007/s00784-017-2240-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in maxillomandibular morphology among patients with mucopolysaccharidoses I, II, III, IV and VI: a retrospective MRI study

Abstract: Clinicians should be aware of specific differences in mandibular morphology and condylar involvement among the MPS subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 42 publications
4
19
0
Order By: Relevance
“…In fact, many of the MPS patients develop a severe open bite causing impaired bite function, uneven tooth wear and limited mouth opening. It is therefore important to recognize that the mandibular morphology of MPS patients significantly differs not only as compared to those of individuals without MPS but also among MPS subtypes 14 . This finding is in line with our results, suggesting that condylar resorption is more frequent and more severe in MPS I patients than in those of MPS II and IV individuals.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In fact, many of the MPS patients develop a severe open bite causing impaired bite function, uneven tooth wear and limited mouth opening. It is therefore important to recognize that the mandibular morphology of MPS patients significantly differs not only as compared to those of individuals without MPS but also among MPS subtypes 14 . This finding is in line with our results, suggesting that condylar resorption is more frequent and more severe in MPS I patients than in those of MPS II and IV individuals.…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting that we observed condylar changes in all MPS I patients irrespective of patients' age, which indicates that this finding has an early onset in MPS I. Indeed, we have previously observed that condylar resorption in MPS I patients can occur from up to 4 years of age 14 . Another relevant finding of our present study is that condylar resorption also exists in the mild MPS I‐Scheie form.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations